The Hermeneutic Circle of Data Visualization: The Case Study of the Affinity Map. - Rodighiero, Dario; Romele, Alberto (Techné: Research in Philosophy & Technology, 2020)
In this article, we show how postphenomenology can be used to analyze the Affinity Map: a data visualization that reveals the hidden dynamics that exist between individuals within large organizations. We make use of the Affinity Map to expand the classic postphenomenology that privileges a ‘linear’ understanding of technological mediations and introduce the notions of ‘iterativity’ and ‘collectivity.’ In the first section of the paper, we discuss both classic and more recent descriptions of humantechnology-world relations in order to transcendentally approach the discipline of data visualization. In the second section, we use the Affinity Map case study to consider three elements: 1) the collection of data and the design process; 2) the visual grammar of the data visualization, and 3) the process of self-recognition for the map ‘reader.’ In the third section, we introduce the hermeneutic circle of data visualization. Finally, we suggest that the Affinity Map, because of its ethical and political multistability, might be seen as a material encounter between postphenomenology, actor-network theory (ANT), and hermeneutics.